Calculation of the Effective Diffusion Coefficients in Drying of Chemical and Mechanical Pretreated Rosehip Fruits (Rosa eglanteria L.) With Selected Mass Transfer Models - Mabellini, Alejandra (2013)
The aim of this work was to select models of mass transfer to estimate effective mass diffusion coefficients during the dehydration of Rosa eglanteria fruits with air at 70°C. Fruits were pretreated chemically and mechanically (dipping it in NaOH and ethyl oleate solutions and cutting or perforating the fruit cuticle). Selected models were those of Becker and Fick?s second law, considering fruit shrinkage during drying. Both models satisfactorily predict the fruit drying, and the different pretreatments, to total or partially remove this waxen cuticle, noticeably improved water diffusion, reducing the time of processing from 28% (NaOH) to 52% (oleate and mechanical pretreatments). Mechanical pretreatments were the more effective, because oleate presents quality problems.